2009
DOI: 10.1007/s00167-009-0864-3
|View full text |Cite
|
Sign up to set email alerts
|

The role of anterior cruciate ligament reconstruction in the older patients, 55 years or above

Abstract: Anterior cruciate ligament (ACL) deficiency can result in symptomatic functional instability of the knee regardless of the patient's age. We reviewed a single surgeon database of 908 ACL reconstructions carried out in the last 20 years for symptomatic instability. 14 patients were identified who were 55 years or above at surgery (mean: 60 years, range 55-75 years). Patients were evaluated clinically and with clinical outcome scoring and KT-1000 arthrometry assessment. 12 patients (86%) were available to attend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
28
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 45 publications
2
28
0
Order By: Relevance
“…This is in line with Osti et al who reported comparable clinical outcomes in middleaged patients and in patients aged below 30 (Osti et al, 2011). Furthermore, this is also supported by Arbuthnot et al who reported that ACL reconstruction using autograft in patients above 55 years improves functional outcome scoring and permits a return to a reasonable level of activity, although not to pre-injury levels (Arbuthnot & Brink, 2010).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This is in line with Osti et al who reported comparable clinical outcomes in middleaged patients and in patients aged below 30 (Osti et al, 2011). Furthermore, this is also supported by Arbuthnot et al who reported that ACL reconstruction using autograft in patients above 55 years improves functional outcome scoring and permits a return to a reasonable level of activity, although not to pre-injury levels (Arbuthnot & Brink, 2010).…”
Section: Discussionsupporting
confidence: 86%
“…Furthermore, this is also supported by Arbuthnot et al. who reported that ACL reconstruction using autograft in patients above 55 years improves functional outcome scoring and permits a return to a reasonable level of activity, although not to pre‐injury levels (Arbuthnot & Brink, ).…”
Section: Discussionmentioning
confidence: 56%
“…Abstracts of studies obtained during the search were reviewed in duplicate by 2 of the authors to determine appropriateness for inclusion in the study, with full-text review performed when questions existed as to whether the study should be included in analysis. There were 12 studies 1 - 7 , 12 , 17 , 23 , 24 , 29 that met the final criteria and were included in the final data analysis ( Figure 1 ). These studies had their reference lists reviewed for additional papers appropriate for inclusion, with no additional studies selected.…”
Section: Methodsmentioning
confidence: 99%
“…If arthritis is present in an ACL-deficient knee, it may be a relative contraindication to ACL reconstruction. 1 , 21 Older individuals have a greater likelihood of developing arthrofibrosis. 11 , 13 , 31 However, active patients are not satisfied with activity restraint.…”
mentioning
confidence: 99%
“…Similar good results have been reported by other authors. 7 8 9 Studies that have compared outcomes of ACL reconstruction in patients younger and older than 40–50 years of age have demonstrated outcomes comparable in both the groups. 10 11 12 13 Cartilage degeneration, although present to a greater degree in the older cohort, was not associated with a poorer outcome at intermediate followup.…”
Section: Discussionmentioning
confidence: 99%